The Effectiveness of the Implementation of the Policy of Direct Cash Assistance – Village Funds for the Community in Anggana District, Kutai Kartanegara Regency - Apriani, Fajar; Juleha, Titin (Budapest International Research and Critics University, 2021)
The Direct Cash Assistance Policy - Village Fund is the government's effort in dealing with poverty due to the impact of the Covid-19 pandemic by utilizing the village budget. Anggana Sub-district is one of the sub-districts on the coast of Kutai Kartanegara Regency that implements it. This research aims toanalyze the effectiveness of the implementation of the Direct Cash Assistance - Village Fund policy during the pandemic for the people of Anggana District, Kutai Kartanegara Regency. Qualitative analysis was carried outon the three factors that determine the success of policy implementation, namely the logic of the policy, the policy environment and the ability of the implementor to implement the policy. The location of this research includes four of the eight villages in Anggana District, namely Sidomulyo, Kutai Lama, Anggana and Sungai Meriam villages. The results showed that the implementation of the Direct Cash Assistance - Village Fund policy in Anggana District had been carried out quite effectively because it contributed to reducing poverty during the Covid-19 pandemic. This is seen from the aspect of policy logic which contains alternative problem-solving content that appropriate in overcoming the negative impact of the Covid-19 pandemic on the community's economy through collaboration between the Central Government and Regional Governments. From the aspect of the policy environment, there is a conducive environment to support the smooth implementation of the program, both internal and external policies. Meanwhile, from the aspect of the ability of policy implementers, the conditionThe Village Government in terms of competence and quite limited quantity does not really hinder the proper management of Village Funds in the BLT-DD program during 2020 to 2021, even though the distribution of BLT-DD is still not in accordance with the specified period as stated in the Technical Instructions BLT-DD.